2009
DOI: 10.1111/j.1749-6632.2009.04676.x
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Immunogenetic Features and Photosensitivity of Cutaneous Lupus Erythematosus from the Aspect of Japanese Studies

Abstract: Skin lesions of collagen diseases are influenced by environmental triggers, such as UV light, and are variable in cutaneous lupus erythematosus (LE), such as systemic LE (SLE), chronic discoid LE (CDLE), subacute cutaneous LE (SCLE), and LE tumidus (LET). Although there are a few conflicting reports on photosensitivity in collagen diseases, many Japanese dermatologists feel there are photosensitivity differences in LE between Asians and Caucasians with SCLE and LET. To address this issue, we have carried out g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…There is evidence that genetic and environmental factors are involved in the pathogenesis of this complex disease (1116). Genetic associations have been reported in patients with CLE including polymorphisms of genes encoding HLA, TNF-α, and complement molecules (1215).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that genetic and environmental factors are involved in the pathogenesis of this complex disease (1116). Genetic associations have been reported in patients with CLE including polymorphisms of genes encoding HLA, TNF-α, and complement molecules (1215).…”
Section: Discussionmentioning
confidence: 99%
“…Those patients with photosensitivity comprised 38.9% of all patients in our study (SLE: 18/34 cases, CLE: 2/15 cases), whereas a recent survey of Japanese patients revealed that 59% (49/83 cases) of SLE and 39% (12/31cases) of chronic discoid LE (CDLE) patients had photosensitivity, which was determined by standard clinical examinations, including the medical histories of the patients. 21 Biazar et al reported that 71.6% of 1002 patients with CLE (1001 from European countries and one from Brazil) were photosensitive according to the patients' history. 22 Previous reports demonstrated a weak correlation between a poor QOL with younger age, 2 but no connection between the QOL and current age.…”
Section: Evaluation Of Qol Of Le Patients With Cutaneous Lesions In Jmentioning
confidence: 99%
“…Among Caucasians, an association with HLA‐DRB1*15:01 and DR3 has been observed (Grumet et al ., ; Davies et al ., ). A significant increase in HLA‐B1*15:01 has been observed in the Japanese (Dong et al ., ; Hashimoto et al ., ; Furukawa et al ., ), Korean (Hong et al ., ) and Taiwanese populations (Pan et al ., ). An association with HLA‐DRB5*01:01 also has been observed in Japanese populations (Hashimoto et al ., ).…”
Section: Introductionmentioning
confidence: 99%